2020
DOI: 10.3389/fmed.2020.00528
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intraoperative Dexmedetomidine Dose on Postoperative First Night Sleep Quality in Elderly Surgery Patients: A Retrospective Study With Propensity Score-Matched Analysis

Abstract: Background: Postoperative sleep disorder is common in elderly surgery patients, and it often worsens their recovery after surgery. This study aimed to explore the effect of intraoperative dexmedetomidine dose on postoperative sleep quality. Methods: Based on information regarding dexmedetomidine use during surgery from an electronic medical record system, 4,349 elderly surgery patients were divided into three groups: 1,374 without intraoperative use of dexmedetomidine (Non-DEX), 917 with dexmedetomidine 0.1-0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…As for the different time point, the DEX was used during the surgery for sedation in nine studies, 5 , 7 , 10 , 15–18 , 21 , 26 as an adjuvant for the regional block in one studies, 22 for postoperative analgesia in nine studies 8 , 12–14 , 19 , 23–25 , 27 and both in surgery and after surgery in eight studies. 9 , 11 , 20 And in 2 retrospective study 15 , 16 and one RCT 25 compared the effect of sleep quality of low dose of DEX (<0.2 μg/kg/h) and high dose (>0.2 μg/kg/h). As for other RCT studies, nine studies used DEX at a low dose and ten studies used DEX at a high dose.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the different time point, the DEX was used during the surgery for sedation in nine studies, 5 , 7 , 10 , 15–18 , 21 , 26 as an adjuvant for the regional block in one studies, 22 for postoperative analgesia in nine studies 8 , 12–14 , 19 , 23–25 , 27 and both in surgery and after surgery in eight studies. 9 , 11 , 20 And in 2 retrospective study 15 , 16 and one RCT 25 compared the effect of sleep quality of low dose of DEX (<0.2 μg/kg/h) and high dose (>0.2 μg/kg/h). As for other RCT studies, nine studies used DEX at a low dose and ten studies used DEX at a high dose.…”
Section: Resultsmentioning
confidence: 99%
“…And 6 of these studies showed that perioperative use of DEX increased the incidence of hypotension or significantly lowered blood pressure compared to the controls group. [11][12][13]15,24,25 The other 6 studies did not find associations between the use of DEX and hypotension. 14,17,19,23,26,27 Nine studies compared the effect of perioperative DEX versus the control group on postoperative bradycardia.…”
Section: Cardiovascular Eventsmentioning
confidence: 99%
“… 17 18 Furthermore, in elderly patients, intraoperative DEX use can remarkably improve the first night sleep quality after surgery, resulting in PD prevention. 19 DEX has been used safely not only in our patient but also in another super-old patient. 20 Briefly, DEX can be a useful anaesthetic adjuvant for a wide range of clinical applications due to its safety and effectiveness.…”
Section: Discussionmentioning
confidence: 57%
“…Moreover, DEX exhibits neuroprotective effects and decreases the incidence of PD,16 leading to shorter hospital stays 17 18. Furthermore, in elderly patients, intraoperative DEX use can remarkably improve the first night sleep quality after surgery, resulting in PD prevention 19. DEX has been used safely not only in our patient but also in another super-old patient 20.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, recent studies have suggested that intraoperative dexmedetomidine infusion is associated with lower incidence of postoperative acute kidney injury, diminished opioid consumption, and shorter extubation time and hospital stay in older adult patients [1]. It may also improve the quality of the first night's sleep following surgery [2][3][4].…”
Section: Introductionmentioning
confidence: 99%